Lower-Body Power, Body Composition, and Agility Performance Among Youth Badminton Athletes - Naufal Hasyim, Rafif Rifqi; Bahri, Samsul; Muhammad, Mar’ie; Juniarsyah, Agung Dwi (Institut Teknologi Bandung, 2025)
Agility is an important component in badminton. Agility is the ability to move with speed and accuracy to reach the shuttlecock in various corners of the court. This study aims to analyze the correlation between lower-limb power and body composition on agility performance in badminton athletes. Participants were 27 female badminton athletes aged 15.44 ± 0.97 years. Body composition (height, body fat percentage - BF%, body mass, BMI, skeletal whole body muscle - SM%), countermovement jump - CMJ, and t-test agility was measured. The data was analyzed using descriptive statistics, Spearman correlation test and hierarchical multiple regression. Spearman correlation test showed that there was no significant relationship with agility (r = -0.40, p = 0.884). Hierarchical regression analysis showed that age, body composition, and CMJ only explained 17.4% of the variance in agility, with a statistically insignificant contribution (ΔR² = 0.019, p = 0.483). Among the independent variables, BF% had a strong positive relationship with body mass (r = 0.763, p < 0.01), indicating that the higher BF%, the higher the body mass. Meanwhile, SM% had a significant negative correlation with BF% (r = -0.498, p < 0.01) and body mass (r = -0.506; p < 0.01), indicating that the higher SM%, the lower the BF% and body mass. Although the variables tested did not contribute significantly to agility, various previous studies have shown that training programs such as plyometrics, core strength training, and Velocity-Based Resistance Training (VBRT) are effective in increasing lower-limb power, which also affects agility. Keywords: agility, body fat, skeletal muscle, lower-limb power, CMJ, youth, badminton